PENINGKATAN MOTIVASI DAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS VIII SMPN 23 PEKANBARU MELALUI METODE HYPNOLEARNING: (Improving Students’ Motivation and Learning Outcomes in English at Grade VIII of SMPN 23 Pekanbaru by Using Hypnolearning Method) - Syofianis Syofianis; Marhamah Marhamah; Yulianto Yulianto (Perspektif Pendidikan dan Keguruan, 2016)
This study aims to improve students’ motivation and learning outcome in English by usingHypnolearning method. This research is a classroom action research (CAR) whereresearchers along with collaborators working together in designing learning scenarios,action, data analysis and reflection. Subjects of the study were students of class VIII SMPN23 Pekanbaru academic year 2015/2016 which the total number was 28 students. Thisresearch was conducted in two cycles following the procedure classroom action research -planning, action, observation and reflection. The first cycle consisted of five meetings, whilethe second cycle consisted of four sessions. Data acquisition was done through observation,field notes, interview and test. The study states that the method hypnolearning improvedmotivation and learning outcomes of English. Indicators increased motivation and learningoutcomes can be seen from the active participation of students in the learning process andlearning outcomes can be seen from the test evaluation. An increase of 25% from 71.43% incycle 1 to 96.43 in cycle 2. The average value of the class also experienced a good increase72.85% to 83.85%. Hypnolearning also made students more relaxed and confident in thelearning process